Everyday resilience: Rural communities as agents of change in peatland social-ecological systems. (December 2022) - Flood, Kate; Mahon, Marie; McDonagh, John
Abstract: The ability to maintain livelihoods in the face of major environmental, political, economic and social stresses is fundamental to building resilient social and ecological communities. This research examines the place community has in this challenge and specifically the role of community involvement in the conservation of peatland social-ecological systems. It explores transformative change at local levels and the relational networks, diverse economies and range of resources communities draw on to achieve this change. Evidence is drawn from a survey, interviews and three case studies of rural community groups in the Irish midlands to provide an overview of local dynamics in peatland conservation and wider issues of place-based development and adaptation. Drawing on theoretical insights from resilience, resourcefulness and diverse economies scholarship, this research reveals the role of local communities in both adapting to, and enacting, change through everyday forms of resilience that are commonplace and ubiquitous in people's lives yet often invisible and under-valued. Thematic areas are identified which provide insights into how communities are: engaging in diverse work practices that foster ecological livelihoods and planetary well-being; co-creating community science projects through local networks and multi-level partnerships; and developing management and stewardship cultures that emphasise collaboration, co-operation and the commons. This research will help actors at a variety of scales to plan and implement more collaborative and inclusive research and restoration programs for peatland conservation. It also has relevance for regions with landscapes in transition that seek to initiate equitable community capacity-building programs and diverse economies in the shift from extractive to regenerative land use. These transitions will require investment and resources both for ecosystem restoration and the relational networks that are so crucial to the work of building the collaborative communities, cultures and economies of the future. Highlights: Provides empirical evidence of the importance of local communities and knowledge systems for the conservation of peatlands. Highlights the value of relational networks in building the collaborative communities, cultures and economies of the future. Suggests framework to recognise and resource these relational networks and mobilise capacity-building programs. Provides inventory of the diverse economies and ecological livelihoods key to sustainable, resilient and just transitions. Recommends fostering collaborative, equitable research and restoration programs to build social and ecological resilience.